Does cognitive inflexibility predict violent extremist behaviour intentions? A registered direct replication report of Zmigrod, Rentfrow, & Robbins, 2019. (6th December 2020) - Schumann, Sandy; Salman, Nadine L.; Clemmow, Caitlin; Gill, Paul
Abstract : Purpose: Research assessing violent extremist risk factors thus far largely ignored the role of cognitive processes. Zmigrod and colleagues (2019a) addressed this gap and presented first systematic evidence that lower levels of cognitive flexibility predict a higher willingness to fight and, ultimately, die for a national ingroup. This finding has important theoretical and practical implications. In order to strengthen the potential contribution of Zmigrod et al.'s work, we will conduct a registered direct replication of Study 1. Extending the original study, we further examine whether the documented relationship still holds when a self‐report measure for cognitive flexibility is introduced and when analyses control for identity fusion. We also investigate if cognitive inflexibility solely predicts violent or also normative pro‐group behaviour intentions. Methods: Following Zmigrod, Rentfrow, and Robbins (2019a), we will administer a cross‐sectional survey study. Participants ( N  = 1, 378) report their willingness to fight, die, and sacrifice themselves for the ingroup and complete the Remote Associates as well as Wisconsin Card Sorting tests. Afterwards, additional measures of self‐reported cognitive flexibility, identity fusion, and normative pro‐group behaviour are assessed. Results: To be completed. Conclusions: To be completed.